Effects of fluticasone propionate and budesonide on the expression of immune defense genes in bronchial epithelial cells. (June 2018) - van den Berge, M.; Jonker, M.R.; Miller-Larsson, A.; Postma, D.S.; Heijink, I.H.
Abstract: Background: COPD patients have increased risk of pneumonia when treated with fluticasone propionate (FP), whereas this is generally not the case with budesonide (BUD) treatment. We hypothesized that BUD and FP differentially affect the expression of immune defense genes. Methods: Human bronchial epithelial 16HBE cells and air-liquid interface (ALI)-cultured primary bronchial epithelial cells (PBECs) were pre-treated with clinically equipotent concentrations of BUD or FP (0.16–16 nM BUD and 0.1–10 nM FP), and the expression of immune defense genes was studied at baseline and after exposure to rhinovirus (RV16). Results: Using microfluidic cards, we observed that both BUD and FP significantly suppressed CXCL8, IFNB1 and S100A 8 mRNA expression in unstimulated 16HBE cells. Interestingly, BUD, but not FP, significantly increased lactotransferrin (LTF) expression. The difference between the effect of BUD and FP on LTF expression was statistically significant and confirmed by qPCR and at the protein level by western blotting. RV16 infection of ALI-cultured PBECs significantly increased the expression of CCL20, IFNB1 and S100A8, but not of LTF or CAMP / LL-37 . In these RV16-exposed cells, LTF expression was again significantly higher upon pre-treatment with BUD than with FP. The same was observed for S100A 8, but not for CCL20, IFNB1 or CAMP / LL-37 expression. Conclusions: Treatment of human bronchial epithelial cells with BUD results in significantly higher expression of specific immune defense genes than treatment with FP. The differential regulation of these immune defense genes may help to explain the clinical observation that BUD and FP treatment differ with respect to the risk of developing pneumonia in COPD.